Sino-Japan relations : clashes of the Asian giants. - Lim, Hui Kwan. (2008)
Territorial conflicts and incursions, Japan's alliance with the US, Japan's position on the Taiwan Strait issue and war history have direct impact on Japan-China relations. The optimism of the Sino-Japanese relationship is overrated due to limitations of economic interdependence and institutions.